Analisis Yuridis Tindak Pidana Perdagangan Manusia Perlindungan Terhadap Korban Serta Upaya Pencegahannya Di Indonesia (Berdasarkan Undang-undang No 21 Tahun 2007) - Pratikno, Muhammad Wisnu Raka (Peneliti.net, 2024)
Human trafficking, also known as “trafficking,” is a practice involving the transportation, sale, or exploitation of human beings, especially women and children, in violation of human rights. This phenomenon has existed since ancient times and continues to develop in increasingly complex forms in the era of globalization, becoming a serious issue with detrimental economic, political, cultural and humanitarian impacts. Indonesia, with its large population and geographical complexity, is a fertile ground for this practice, both as a country of origin and transit. Women and children are the main victims, with an alarming increase in cases. The Indonesian government has taken concrete steps, including passing Law Number 21 of 2007 concerning the Elimination of TIP, as an effort to prevent, protect and rehabilitate victims. Protection of crime victims, especially human trafficking, involves prevention, law enforcement, rehabilitation, reintegration and recovery efforts, and requires cross-sectoral and cross-border cooperation. Law Number 21 of 2007 aims to provide legal protection for victims, including through restitution as part of the legal process, placing victim recovery as a top priority in law enforcement. Apart from that, prevention efforts also require outreach and education to the community to increase understanding about human trafficking and the rights of victims and create an environment that is not conducive to the practice of human trafficking. Cooperation between government, non-governmental organizations, civil society and international institutions is important to create a safe and fair environment for victims and prevent future human trafficking practs.